STUDENTS’ PERSPECTIVES ON THE USE OF KAHOOT IN ENGLISH LEARNING MOTIVATION AT GRADE 10 OF SMA YP HKBP PEMATANGSIANTAR - Sinambela, Chintya; Pangaribuan, Silvia; Sinambela, Chintya Angelina; Pangaribuan, Yemima; Silalahi, Dumaris E (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2025)
English is an international language that plays an important role in communication, education, and future career development. However, many Indonesian students still struggle with low motivation when learning English because teaching practices are often teacher-centered and lack interactive media. To address this issue, this study explored Grade 10 students’ perspectives on the use of Kahoot! as a game-based learning platform to enhance their motivation in English learning at SMA YP HKBP Pematangsiantar. This research employed a quantitative descriptive method with a survey design, using a Likert-scale questionnaire administered to 16 students who had experienced Kahoot!-based activities. The findings revealed that 68.75% of the students showed very positive perceptions toward Kahoot!, indicating that the platform increased their excitement, participation, and enjoyment during English lessons. Students also reported improvements in cognitive, affective, and psychomotor aspects of learning, suggesting that Kahoot! made the classroom atmosphere more active, engaging, and student-centered. Overall, the study concludes that Kahoot! effectively enhances students’ learning motivation by offering a fun, competitive, and interactive learning experience. Therefore, integrating Kahoot! into English classrooms is recommended as a strategy to improve students’ motivation and encourage their active involvement in learning.